Analisis Manajemen Risiko Berbasis ISO 31000 pada Studi Kasus Hotel Jakarta di Balikpapan - Reza Fahlevi, Mohammad; Rahmawati, Febri; Mira Detavia, Andi; Vaneza Sihaloho, Julice; Fadillah, Nur; Lolo Padang, Elifas; Deny Arthawan Sugih Prabowo, I Putu (SPECTA Journal of Technology, 2025)
The study aims to analyze the implementation of ISO 31000-based risk management at Jakarta Hotel in Balikpapan which faces various challenges in its operations. Risk management is an important component in undergoing the sustainability of hotel operations, especially in the hospitality sector which is faced with economic, regulatory, and reputational risks. A structured risk management approach is needed to mitigate those risks and ensure the hotel can operate optimally. SWOT and PESTLE analysis are the research methods used in understanding the internal and external conditions of Hotel Jakarta, which are then followed by the ISO 31000-based risk management process, namely risk identification, risk analysis, risk evaluation, and risk treatment. The results show that Hotel Jakarta faces various risks, including operational risks related to the lack of digitalization, economic risks due to cash flow instability, and reputational risks caused by negligence in guest services. The proposed mitigation strategies include digitizing the hotel's management system, collaborating with external partners, and improving employee training and competency. The implementation of ISO 31000-based risk management helps the hotel in minimizing the negative impact of risks and improving readiness in facing future challenges. Overall, this study confirms the importance of implementing a structured risk management framework to improve operational sustainability and customer satisfaction.